Violent affections: queer sexuality, techniques of power, and law in Russia - Kondakov, Alexander (Fringe, 2022)
Violent Affections uncovers techniques of power that work to translate emotions into violence against queer people. Based on analysis of over 300 criminal cases of anti-queer violence in Russia before and after the introduction of 'gay propaganda' law, the book shows how violent acts are framed in emotional language by perpetrators during their criminal trials. It then utilises an original methodology of studying 'legal memes' and argues that these individual affective states are directly connected to the political violence aimed at queer lives more generally